(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
The European Central Bank (ECB), like the rest of the world’s major central banks, has sought to cut interest rates as an attempt to stimulate the Eurozone economy ( of which Greece is a part ) . Accordingly, this study aimed to analyze the effect of this reduction on the Greek economy؛ by highlighting : the Greek interest rate policy before and after the euro, crisis and its causes, as well as the consequences of the austerity plans that Greece continues to apply until now. After presenting the theoretical aspects of the subject of our research, the changes in both the basic interest rates ( bank rate ) and the main indicators of the Greek economy (GDP growth rate, inflation rate and unemployment rate), were analyzed, both graphically and statistically. The study concluded that although the basic interest rates have a significant effect on each of the indicators mentioned above, the ECB policy of reducing interest rates did not achieve the desired results for Greece.